Alternatives to incarceration: Commnity-based alternatives for juveniles - Darnell, Sandra K. (American journal of criminal justice, 1980)
This research deals with the problems associated with the juvenile rehabilitative efforts in the United States today. Using the recidivism rates for juveniles, the studies by Zingraff on resocialization, and Zimbardo’s Stanford House experiment, this paper seeks to show that the present form of institutionalization and treatment is not conducive to rehabilitating the juvenile offenders. Communitybased corrections is suggested as alternatives to the failing present system. The alternatives discussed include diversion strategies such as Project Crossroads in Washington, B.C. and the Sacramento 601 Diversion Process in California. Other alternatives given include group homes such as the Highfields Project and the Silverlake Experiment, foster homes, and family homes. Correctional day care centers are also a viable alternative to incarceration. The GUIDE Program in California, and the Parkland Project in Kentucky, and the Utah Pinehills Experiment are examples of this type of Program. Halfway houses are also used to help juveniles adjust to society and to prevent them from having to submit to total incarceration. Advantages and disadvantages to each of these alternatives are provided. Although some of these experiments have failed, these efforts appear to be less costly, more effective, and less damaging than institutionalization of offenders.